Species delineation and hybrid identification using diagnostic nuclear markers for Mediterranean groupers Epinephelus marginatus and Mycteroperca rubra - He, Song; Bariche, Michel; Pombo-Ayora, Lucía; Berumen, Michael L. (Frontiers in Marine Science, 2024)
Globally, groupers (Serranidae) are commercially important fish species. Hybridization within this family has been reported in captivity and natural environments, usually among congeneric species. However, intergeneric hybridization has been reported only occasionally. Given the commercial interest in these fish, artisanal or recreational fishermen easily notice “weird-looking” individuals. This is the case of an unidentified grouper noticed by a spearfisher in Lebanese Mediterranean waters. Visual comparisons raised the possibility that the observed specimen was a hybrid. Molecular analysis based on two mitochondrial and three nuclear markers was performed to investigate this potential hybrid’s affinity. The discordance of the phylogenetic gene trees of the mitochondrial and nuclear markers indicates that E. marginatus and M. rubra are potential parent species of a hybrid individual in our samples. The subsequent haploweb analysis based on the S7 nuclear marker reveals the affinity of the hybrid individual to both E. marginatus and M. rubra. In this specific hybridization case, the nuclear marker S7 emerges as a valuable diagnostic tool for species delineation and hybrid detection.